Pelatihan Pemadaman Kebakaran Dilingkungan Rumah - Dedi Rianto; Richard Jokhu, Jean; Mifta Farid, M; wijonarko, wijonarko; Hilda, Hilda (Lentera Jurnal Pengabdian Masyarakat, 2023)
Fires can occur in the home environment due to the use or carelessness in using electrical equipment, gas stoves, burning rubbish, cigarette butts. Often people don't know how to handle it if a fire occurs. We provide training to the community on how to deal with a fire in their home environment. This activity aims to provide basic education and understanding in dealing with fires in the home environment using standard fire equipment. The public is also invited to know the factors that cause fires and how to deal with them without causing panicThe results of the training show that some people do not understand the factors that cause fires and how to deal with them. After being given training and education, the community understands the causes of fires and how to deal with them if a fire occurs. The public is invited to practice how to extinguish fires using wet sacks and fire extinguishers.